2021
DOI: 10.14218/jcth.2021.00228
|View full text |Cite
|
Sign up to set email alerts
|

Critical Update on the Diagnosis and Management of COVID-19 in Advanced Cirrhosis and Liver Transplant Recipients

Abstract: The novel coronavirus disease 2019 (COVID-19) pandemic has impacted health care worldwide, with specific patient populations, such as those with diabetes, cardiovascular disease, and chronic lung disease, at higher risk of infection and others at higher risk of disease progression. Patients with decompensated cirrhosis fall into the latter category and are a unique group that require specific treatment and management decisions because they can develop acute-on-chronic liver failure. In liver transplant recipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 124 publications
(245 reference statements)
0
4
0
1
Order By: Relevance
“…A similar observation in a larger group of patients showed an increased number of hospitalizations among patients with AH and ALD during the COVID-19 pandemic. Furthermore, the mortality in the course of ALD compared to pre-pandemic years was greater, too [225,226].…”
Section: Coronavirus In Ald Patientsmentioning
confidence: 97%
“…A similar observation in a larger group of patients showed an increased number of hospitalizations among patients with AH and ALD during the COVID-19 pandemic. Furthermore, the mortality in the course of ALD compared to pre-pandemic years was greater, too [225,226].…”
Section: Coronavirus In Ald Patientsmentioning
confidence: 97%
“…The standard treatment for COVID-19 infection of different severity can be administered to LT recipients, albeit cautiously[ 53 , 54 ]. In most cases, it is advised to maintain immunosuppression, preferably the minimum effective regimen, to prevent rejection and aid recovery from COVID-19[ 55 ]. Systematic reviews and meta-analyses showed that the most commonly used immunosuppressant in LT recipients with COVID-19 were calcineurin inhibitors (CNI), followed by antimetabolites like mycophenolate mofetil (MMF), and finally corticosteroids.…”
Section: Covid-19 Treatment In Lt Recipientsmentioning
confidence: 99%
“…It is recommended to decrease but not stop CNI in LT recipients with COVID-19-related lymphopenia, fever, or deteriorating pulmonary status[ 58 ]. In patients with renal impairment, it is recommended to use a higher corticosteroid dose while reducing or stopping CNI until kidney functions are normalized[ 55 ].…”
Section: Covid-19 Treatment In Lt Recipientsmentioning
confidence: 99%
“…The disease was first discovered on December 19, 2019, in Wuhan, China [1], which was later declared as a public health emergency by the World Health Organization (WHO) on January 30, 2020. This viral pandemic spreads through respiratory droplets via sneezing and coughing and has an incubation period of approximately 3-5 days [2]. The most common clinical manifestations of COVID-19 are fever, cough, dyspnea, fatigue, myalgia, and gastrointestinal symptoms [3].…”
Section: Introductionmentioning
confidence: 99%